Karakteristik, Komponen, dan Struktur Sistim Informasi Manajemen Pendidkan serta Program Pengembangan Sistim Informasi Manajemen Pendidikan - Elvarisna, Elvarisna; Misrawani, Misrawani; Sari, Rahmi; Faziz, Muhammad (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to determine the characteristics, components, and structure of the education management information system and the development program of the education management information system. This study uses the literature review method as the main approach. The steps taken in this literature study include Source Identification, Literature Selection Criteria, Data Analysis and Synthesis, and Literature Validation and Triangulation. The results of the data analysis indicate that the Education Management Information System (SIMDIK) is a system specifically designed to assist educational institutions in managing information effectively, efficiently, and accurately. SIMDIK supports managerial and operational functions through the collection, processing, storage, and presentation of data. The main characteristics of SIMDIK include system integration, real-time capability, high accuracy, and support for decision-making. These characteristics enable educational institutions to enhance the quality of governance comprehensively. The components of SIM consist of Hardware, Software, Database, Work Procedures, Human Resources (brainware), and Networks and Communication. The development of educational data and information heavily relies on data digitization, input quality, and the utilization of analytical technology to support evidence-based education evaluation and planning.